Cardiac Cachexia dan Dampaknya terhadap Sintasan Penderita Gagal Jantung - Aninka Saboe; Badai B. Tiksnadi; Augustine Purnomowati; Toni M. Aprami (The Indonesian Heart Association, 2015)
Background. Cardiac cachexia (CC) is one of indicator of poor prognosis in heart failure. Unfortunately, its existence is often overlooked by many cardiologists, this is further complicated by small number of study concerning CC, and the controversial issues they encompasses.Methods. The aim of this study is to analyze the survival in heart failure (HF) patients with cachexia complications. A retrospective cohort study was conducted on the data from Hasan Sadikin General Hospital HF registry from March 2013 – August 2014. The inclusion criteria was the data registry (registry’s inclusion criterias: HF patients above 18 years of age with left ventricle ejection fraction (LVEF) below 40%, time onset of HF more than 6 months and exclusion criterias were valvular diseases as primary etiology of HF). The exclusion criteria was if the patients have other chronic disease (COPD, CKD, cancer). Cardiac cachexia was diagnosed in patients fulfilling the criteria from international cachexia consensus.Results. There were 39 patients, most of them were female (61.5%), with mean LVEF 28.5% (+6.7). Cardiac cachexia was diagnosed in 6 (15.3%) patients. At 6 months of follow-up after initial enrollment, the cumulative rate of death from cardiovascular cause was 83% among cachectic as compared 37.5% among noncachectic patients p=0.001 Adjusted HR (95%CI) = 8.05 (2.40–27.04). There were no association between mortality with sex (p=0.268), etiology of HF (p=0.288), LVEF (p=0.061), comorbid condition (hypertension p=0.237, diabetes mellitus p=0.163).Conclusions. We conclude that patients with cardiac cachexia is independent predictor of death in HF and warrants a special consideration in the management of HF.